The Dynamic Effect of Unemployment Rate and Crime Rate on Suicide Rate under Economic Growth Rate - Ssu-Han Chen; Tzu-Yi Yang; Yu-Tai Yang; Chiu-Yen Wang (Discrete Dynamics in Nature and Society)
In this study, the panel smooth transition regression model was used for an empirical survey to investigate the dynamic effect of unemployment rate and crime rate on suicide rate under economic growth rate. The research period was from 2000 to 2019. Statistical results indicated that unemployment rate and crime rate had dynamic effects on suicide rate and that nonlinear relationships existed among them. In addition, depending on the fluctuation of dynamic value, the rise or fall of suicide rate had an asymmetrical influence on the value of unemployment rate and crime rate. Finally, when the rate of change of economic growth rate was larger than the dynamic value, the unemployment rate and crime rate had an aggressive influence on suicide rate.